Determination of the creep properties of Pb-free solders for harsh environments using meso-scale testing - Godard Desmarest, S; Johnston, C; Grant, PS (IMAPS - International Microelectronics Assembly and Packaging Society, 2012)
Solder joints in electronic packages are prone to failure due to the evolution of thermal expansion mismatch strains during thermal cycling. The comparatively wide operating temperature range and long lifetimes of aerospace electronics require high reliability solder joints. Since 2006, high reliability industries (aerospace and military amongst others) that are exempt from lead-free RoHS regulation on account of concerns over the reliability of Pb-free solders have found it increasingly difficult and expensive to continue using traditional Sn-Pb-based solders. Hence there is a pressing need to find a suitable alternative that can match the manufacturing and reliability performance of Sn-Pb. There remains a dearth of data for the constitutive behaviour of Pb-free solders under harsh environment scenarios. Unfortunately, conventional test approaches, particularly in the case of creep behaviour which is critical to solder lifetimes, are expensive and time-consuming. High temperature nanoindentation has been recently developed as a quick method for the determination of creep properties of solder alloys. This paper compares and contrasts nanoindentation creep results for bulk Pb-Sn and lead-free solders. However, there are limits to nanoindentation creep, in particular the load-dependence of the technique. A new meso-scale test approach that lies between nanoindentation and bulk creep testing has been developed. Real ball grid arrays using Pb-free solders have been creep tested in the temperature and stress ranges of operating solder joints. High temperature creep constitutive data has been obtained. The technique offers promising time and materials savings in obtaining important mechanical property data for subsequent use in life-prediction models.